Pengaruh Literasi Keuangan dan Sikap Keuangan terhadap Pengelolaan Keuangan - Sri Puji Lestari; Dinda Ariska (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2023)
This study aims to find out how the effect of Financial Literacy and Financial Attitudes on Financial Management of Management Study Program Students, Faculty of Economics and Business, Universitas Muhammadiyah Sumatera Utara. The approach used is descriptive quantitative. The population in this study was 2,440 people, with a sample of 100 people. The research instrument used a questionnaire. Data analysis techniques using SPSS. The results of this study indicate that financial literacy has a significant effect on financial management, financial attitudes have no significant effect on financial management, financial literacy and financial attitudes have a significant effect on financial management.